Painting Restoration “Penangkapan Pangeran Diponegoro” By Raden Saleh Sjarif Boestaman Through The Management Function Approach - Ronang Kennylas Dofi; Mikke Susanto; Dian Ajeng Kirana (TUMATA: Journal of Arts and Cultural Management, 2025)
This research describes the restoration process of the painting Penangkapan Pangeran Diponegoro (1857) by Raden Saleh Sjarif Boestaman using the management function approach (Planning, Organizing, Actuating, and Controlling). Penangkapan Pangeran Diponegoro painting is one of the important and historical works of art for Indonesia. This research aims to analyze each management function applied in the restoration activities. The method used in this research is descriptive qualitative with a case study approach. Data was obtained through interviews and documents of the restoration process conducted in 2012 & 2013 from Susanne Erhards and Adek Wahyuni. The results show that the four management functions have been implemented effectively. However, the long-term preservation aspect still requires further planning so that conservation sustainability is maintained.